Fifteen minute consultation: stabilisaton of the high risk newborn infant beside the mother - Batey, Natalie; Yoxall, B.; Fawke, J.; Duley, Lelia; Dorling, Jon (BMJ Publishing Group, 2017)
Paediatric and adult resuscitation is often performed with family present. Current guidelines recommend deferred umbilical cord clamping as part of immediate neonatal care, requiring neonatal assessment next to the mother. This paper describes strategies for providing care beside the mother using both standard resuscitation equipment and a trolley designed for this purpose.